TIME AND PLACE DISTRIBUTION OFACUTE ENCEPHALITIS SYNDROME (AES) JAPANESE ENCEPHALITIS (JE) CASES IN GORAKHPUR - Singh, G K; Agarwal, Neeraj; Singh, C M; Pandey, Sanjay; Kumar, Pragya; Singh, Kamlesh; Kumar, Gulshan; Verma, Vikas; Gupta, M K (Indian Journal of Community Health, 2013)
Introduction: 1000 children below the age of 15 years died from encephalitis in the states of UP, Bihar and Assam since 1978. JE vaccinations in 2010 and deep bore wells in 60 districts in India are the two preventive measures in use. Hypothesis generation through a time, place distribution study followed by a risk factor study would help target preventive and curative measures. A spatial temporal analysis of the 2012 encephalitis epidemic in the district of Gorakhpur, having the most cases, is reported. Material and Method Government of UP data on 714 cases of AES/JE occurring during 2012 in Gorakhpur district was analysed. Time and place distribution is described. Various hypotheses on mode of transmission besides other important features of the epidemic were generated. Data was used to create video maps of the 2012 AESJE epidemic using Epi-info 7. Onset of symptoms was used on the time axis and longitude-latitude data from residential details was used to describe the place distribution. Videos were interpreted to draw important inferences which may be used in planning a strategy to break the 2013 epidemic Result: Thirty (4.20%) of 714 patients fitting case definitions were confirmed cases of Japanese encephalitis. 148 (20%) died. 669 (93.69%) were below 15 years of age. Male to female ratio was 1.45:1. On 9th Aug 2012 the usual 5 cases per day mark was crossed with 10 cases/day reported. On 22th August the peak of 19 cases/day was reached. On 11th September the epidemic started receding at rates slower than the rise showing multiple spurts. The medical college had 1.5 times the cases than anywhere else. On 10th Dec the daily incidence had returned to under 5 levels. District wise place distribution of the 2009, 2011 and 2012 cases shows Gorakhpur as having 714 i.e. twice the number of cases than anywhere else in 2012. Conclusion: The epidemic is seasonal and perhaps spreads man to man. Mosquito having a life time range of 5 miles cannot spread the virus 30 kms away to the next case. For every case there are about 500 infected children making the number of <15yrs infected as 357000. Given 44, 36, 275 as 2012 population of Gorakhpur and 40% (17,74,510) below 15 years old, 20% were infected and transmitting. A reporting of more than 4 cases near 7.8.12 heralded a dangerous spurt up to 19/day lasting about a month. The epidemic was mainly contributed by the medical college area where incidence rate was highest during the spurt perhaps because of a high case density produced by centripetal referral. Patients need to be treated near their home.